Avaliação da atividade anti-inflamatória do óleo essencial da bergamota em modelo animal de periodontite - MOREIRA, Amanda Pereira (2020)
Periodontitis consists of a chronic inflammatory disease characterized by tissue inflammation associated with progressive loss of gingival insertion, bone resorption and apical migration of the junctional epithelium. Periodontal health needs a controlled immune-inflammatory state that can maintain homeostasis in the microorganism-host relationship; however, in periodontitis, the host's immune response is deregulated. An inflammatory mediator that seems to play a fundamental role in the evolution of periodontitis is nitric oxide (NO), which is a free radical produced from L-arginine by the action of enzymes called nitric oxide synthases. Inflammatory stimuli activate iNOS (inducible nitric oxide synthase) in several cells, including osteoclasts and osteoblasts, resulting in increased production of NO in the tissues and acting on bone resorption. Some therapeutic strategies based on the use of plant extracts have been investigated to modulate the inflammatory response, including periodontitis. From this perspective, bergamot essential oil (BEO) has shown promising results and, therefore, the hypothesis raised in the present study is that the use of BEO has an anti-inflammatory effect and reduces alveolar bone loss suggesting potential adjunctive action in mechanical periodontal therapy in an induced periodontitis model. The anti-inflammatory properties of BEO were evaluated by means of an in vivo study in a model of ligature-induced periodontitis in rats and an in silico analysis of the main compounds of BEO (linalyl acetate and linalool) to verify possible absorption routes, oral bioavailability and toxic effects. A total of 24 male Wistar rats were included in the study and divided into 3 groups: 1) Control Group (n = 8): rats without ligature that received daily gavage with vehicle (DMSO 2%); 2) Ligature group (n = 8): rats with ligature that received daily gavage with vehicle; 3) Ligature + BEO group (n = 8): rats with ligature that received daily gavage with BEO (0.1 ml / kg in vehicle). After 15 days, the animals were sacrificed and samples of gingival tissues around the lower first molars, as well as the hemimandibles, were collected and stored. Analyzes of total protein concentration and nitric oxide production were performed. Bone resorption was evaluated by morphometric method in the mesial region of the first left lower molars. The ANOVA test followed by Tukey was used in the statistical analysis, adopting a significance level of 5%. Regarding the total protein concentration, the ligature and ligature + BEO groups showed a significant increase when compared to the control group (p <0.05). The ligature and ligature + BEO groups also showed higher NO production in the gingival tissue when compared to the control group (p <0.05). Regarding alveolar bone resorption, there was a statistically significant reduction (p <0.05) in the ligature + BEO group when compared to the ligature group. In the in silico analysis, the BEO compounds demonstrate high gastrointestinal absorption and are in accordance with the criteria of the Lipinski rule. Linalyl acetate showed LD50 of 12000 mg / kg and class 6 toxicity. The findings suggest that the use of BEO can reduce alveolar bone loss in rats with ligature-induced periodontitis, even without reducing NO production in the gingival tissue. The main compounds of BEO showed high gastrointestinal absorption, good oral bioavailability and low potential for toxicity.